Nanoparticle‐Based Cu2ZnSn(S, Se)4 Solar Cells With a 9.1% Efficiency Obtained by an Optimization of Sintering Process. Issue 7 (26th June 2017) - Zhang, Yiwen; Satake, Tetsuo; Furuta, Kaoru; Yin, Ming; Sugimoto, Kanta; Suyama, Naoki; Yamada, Akira
Abstract : The sintering process of Cu2 ZnSn(S, Se)4 (CZTSSe) films coated on Mo substrates is optimized by using a selenium/sulfur mixture atmosphere and a designed graphite box. Structural characterization indicates that this optimization is advantageous in reducing the thickness of high resistance Mo(S, Se)2 layer. In addition, Cu content contained in the CdS layer is significantly decreased compared with that obtained by the selenium sintering. An active area efficiency of 9.1% CZTSSe solar cell (without anti‐reflective coating and light soaking) is achieved, demonstrating that the improvement of the Mo/CZTSSe and CZTSSe/CdS interfaces leads to an increased conversion efficiency. Abstract : An active area efficiency of 9.1% Cu2 ZnSn(S, Se)4 solar cell is achieved by the optimization of sintering treatment using a selenium/sulfur mixture atmosphere and a designed graphite box. This optimization effectively inhibits the formation of a thick Mo(S, Se)2 layer and prevents the dissolution and diffusion of Cu atoms from the Cu2 ZnSn(S, Se)4 layer during the CdS layer deposition.